Cardioprotection by acetylcholine: A novel mechanism via mitochondrial biogenesis and function involving the PGC‐1α pathway1. Issue 6 (25th February 2013) - Sun, Lei; Zhao, Mei; Yu, Xiao‐Jiang; Wang, Hao; He, Xi; Liu, Jian‐Kang; Zang, Wei‐Jin
Abstract Mitochondrial biogenesis disorders appear to play an essential role in cardiac dysfunction. Acetylcholine as a potential pharmacologic agent exerts cardioprotective effects. However, its direct action on mitochondria biogenesis in acute cardiac damage due to ischemia/reperfusion remains unclear. The present study determined the involvement of mitochondrial biogenesis and function in the cardiopotection of acetylcholine in H9c2 cells subjected to hypoxia/reoxygenation (H/R). Our findings demonstrated that acetylcholine treatment on the beginning of reoxygenation improved cell viability in a concentration‐dependent way. Consequently, acetylcholine inhibited the mitochondrial morphological abnormalities and caused a significant increase in mitochondrial density, mass, and mitochondrial DNA (mtDNA) copy number. Accordingly, acetylcholine enhanced ATP synthesis, membrane potentials, and activities of mitochondrial complexes in contrast to H/R alone. Furthermore, acetylcholine stimulated the transcriptional activation and protein expression of peroxisome proliferator‐activated receptor co‐activator 1 alpha (PGC‐1α, the central factor for mitochondrial biogenesis) and its downstream targets including nuclear respiration factors and mitochondrial transcription factor A. In addition, acetylcholine activated phosphorylation of AMP‐activated protein kinase (AMPK), which was located upstream of PGC‐1α. Atropine (muscarinic receptor antagonist) abolished the favorable effects of acetylcholine on mitochondria. Knockdown of PGC‐1α or AMPK by siRNA blocked acetylcholine‐induced stimulating effects on mtDNA copy number and against cell injury. In conclusion, we suggested, acetylcholine as a mitochondrial nutrient, protected against the deficient mitochondrial biogenesis and function induced by H/R injury in a cellular model through muscarinic receptor‐mediated, AMPK/PGC‐1α‐associated regulatory program, which may be of significance in elucidating a novel mechanism underlying acetylcholine‐induced cardioprotection. J. Cell. Physiol. 228: 1238–1248, 2013. © 2012 Wiley Periodicals, Inc.